2022
DOI: 10.1002/brb3.2497
|View full text |Cite
|
Sign up to set email alerts
|

The whole‐brain voxel‐based morphometry study in early stage of T2DM patients

Abstract: Aim: This study aimed to investigate the alterations in whole-brain gray matter density in early stage type 2 diabetes mellitus (T2DM) patients with cognitive impairment using magnetic resonance imaging.Methods: Thirty-six cases of early stage T2DM patients with cognitive impairment (T2DM-CI), 34 cases of early stage T2DM patients without cognitive impairment (T2DM) and 30 cases of healthy controls (HC) were enrolled. Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) scores were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have reported decreased DC and node efficiency in ITG ( Chen et al, 2017 ), and cortical atrophy in the ITG has been correlated with cognitive decline in T2DM patients ( Li et al, 2020 ). The inferior frontal junction plays a key role in controlling the spatially global effects of feature-based attention in the human visual area ( Zhang et al, 2018 ), and previous studies have shown abnormal neuronal activity ( Zhang et al, 2022 ) and decreased gray matter volume ( He et al, 2022 ) in the IFG regions in T2DM patients. Therefore, we speculate that impaired ventral visual pathways may be involved in the neural basis of visual cognitive impairment in T2DM patients, particularly visuospatial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported decreased DC and node efficiency in ITG ( Chen et al, 2017 ), and cortical atrophy in the ITG has been correlated with cognitive decline in T2DM patients ( Li et al, 2020 ). The inferior frontal junction plays a key role in controlling the spatially global effects of feature-based attention in the human visual area ( Zhang et al, 2018 ), and previous studies have shown abnormal neuronal activity ( Zhang et al, 2022 ) and decreased gray matter volume ( He et al, 2022 ) in the IFG regions in T2DM patients. Therefore, we speculate that impaired ventral visual pathways may be involved in the neural basis of visual cognitive impairment in T2DM patients, particularly visuospatial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) has also demonstrated the microstructural abnormalities, and the disruption of white matter tracts connecting the frontal, parietal, and temporal regions was related to slowing of information-processing speed in T2DM patients ( Hsu et al, 2012 ; Reijmer et al, 2013 ). In addition, multiple studies have shown reduced gray matter volume and cortical thickness in the cingulate gyrus, superior frontal cortex, inferior temporal and middle occipital cortex in T2DM without MCI ( Zhang et al, 2014 ; Li et al, 2018 ; He et al, 2022 ). Although these studies have demonstrated extensive structural and functional brain damage and were associated with impairment of multiple cognitive domains before the onset of clinical symptoms of MCI in T2DM patients, their findings mostly reflected abnormal changes within local or regional areas of the brain, and the large-scale whole-brain network change patterns in T2DM without MCI remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…With its total automation, standardization, high accuracy, and dependability, voxel-based morphometry (VBM) is a traditional automatic whole-brain analysis approach that allows unbiased research to be performed regarding variations in gray matter between patients and controls ( Ashburner and Friston, 2000 ). The study of the diabetic brain structure has made extensive use of and acceptance of the VBM approach ( Chen et al, 2012 ; García-Casares et al, 2014 ; Liu et al, 2017 ; Wu et al, 2017 ; He et al, 2022 ). According to recent research, patients with AD dementia have higher serum P-tau-181 levels ( Mielke et al, 2018 ), which correlate with the levels of tau protein in the cerebrospinal fluid and can also predict the progression of the disease in participants with normal cognitive function and in patients with mild cognitive impairment ( Janelidze et al, 2020 ; Thijssen et al, 2020 ; Karikari et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%